PERAN HERNIASI LUMBAL TERHADAP TERJADINYA SINDROMA KAUDA EKUINA DAN TINJAUAN TATA LAKSANANYA - Sekplin A. S. Sekeon; David Susanto (Jurnal Sinaps, 2019)
Cauda equina syndrome is a relatively rare neurological disease. This condition is commonly caused by hernia nucleus pulposus. Most of the cauda equina syndrome occurred in lumbar area. Pain is the main symptom with the possibility to be accompanied with autonom disorders such as mixturition and sexual function. Further examination included neuroimaging. The severity of caude equina syndrome depend on the stage of compression level. Management consist of conservative and surgical modalities. In severe cases, early diagnosis and surgery has improved the outcome.